Influence of Cooperative Learning Model of Bamboo Dancing to Students Learning Outcomes in Social Sciences in Elementary School - Sri Rohartati (Universitas Sebelas Maret, 2019)
This research is entitled, The Influence of Cooperative Learning Models Type Bamboo Dancing Against Learning Outcomes of Students in Social Sciences Subjects in Primary Schools. This study aims to describe the implementation and influence of the cooperative model type bamboo dancing on improving student learning outcomes in social science subjects. The research problem formulation was formulated as